2013
DOI: 10.1039/c3cc46543h
|View full text |Cite
|
Sign up to set email alerts
|

Tuning CO2 electroreduction efficiency at Pd shells on Au nanocores

Abstract: The faradaic efficiency of CO2 electroreduction is significantly affected by the thickness of Pd nanoshells on Au cores. The ratio of hydrogen evolution to CO2 reduction was determined by differential electrochemical mass spectrometry. Decreasing the Pd shell thickness from 10 to 1 nm leads to a twofold increase in faradaic efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 28 publications
2
43
0
Order By: Relevance
“…For the CS nanostructures, signals associated with Pd oxide formation and reduction are observed at potentials above 0.7 V. Responses associated with H absorption, hydride formation and hydrogen evolution are observed at potentials more negative than −0.2 V. In the positive scan, signals in the range of 0.0–0.4 V are linked to H desorption from the Pd surface and from within the crystal lattice. The magnitude of the hydrogen‐related signals increases with increasing shell thickness, in agreement with previous studies performed in more acidic solutions . The Pd shells exhibit good stability upon repeated cycles within the potential range investigated.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…For the CS nanostructures, signals associated with Pd oxide formation and reduction are observed at potentials above 0.7 V. Responses associated with H absorption, hydride formation and hydrogen evolution are observed at potentials more negative than −0.2 V. In the positive scan, signals in the range of 0.0–0.4 V are linked to H desorption from the Pd surface and from within the crystal lattice. The magnitude of the hydrogen‐related signals increases with increasing shell thickness, in agreement with previous studies performed in more acidic solutions . The Pd shells exhibit good stability upon repeated cycles within the potential range investigated.…”
Section: Resultssupporting
confidence: 62%
“…Plana et al. showed that the competition between CO 2 reduction and hydrogen evolution shifted significantly towards the latter upon increasing the shell thickness in Au‐Pd core–shell (CS) nanoparticles from 1 to 10 nm . Januszewska et al.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, CO is produced at an industrial scale from a wide variety of materials that includes natural gas, residual oil, petroleum coke and coal. [4][5][6][7][8][9][10][16][17][18][19][20][21][22][23][24] As many as 16 different products have been reported from the electroreduction of CO 2 , 7 thus it is necessary to find catalyst materials with a high selectivity towards a desired product formation. 4,5 A key technological challenge for the electroreduction of CO 2 to CO is to develop a suitable catalyst that is capable of achieving a stable and cost-effective process with high efficiency and selectivity at low overpotentials.…”
Section: Introductionmentioning
confidence: 99%
“…Plana et al [28] studied 1 and 10 nm Pd layers on Au nanoparticles. The faradaic efficiency for CO 2 reduction in a 0.1 M Na 2 SO 4 aqueous solution decreased from 90 to 40 % as the Pd layer grew from 1 to 10 nm.…”
Section: Metal Overlayersmentioning
confidence: 99%